Cost-Effectiveness Analysis of Erythropoietin in Anemia Therapy Strategies for Chronic Kidney Disease Patients Undergoing Hemodialysis: A Systematic Review - Rosi Ami Sari; Seftika Sari; Dwi Endarti; Neni Frimayanti (LPPM Universitas Abdurrab, 2024)
Chronic kidney disease is a significant health issue, with increasing case numbers leading to higher treatment costs. This condition causes decreased kidney function and can result in anemia due to impaired red blood cell production. This study aims to analyze the cost-effectiveness of anemia treatment using Erythropoietin, either as a single therapy or in combination, for patients with chronic kidney failure undergoing hemodialysis. The methods employed include conducting a systematic review to identify problems, establish inclusion and exclusion criteria, and search various databases for relevant studies. The results show that cost-effectiveness varies depending on the Hemoglobin target and the type of Erythropoietin used. In conclusion, setting an appropriate Hemoglobin target and selecting the correct type of Erythropoietin are crucial for effective anemia treatment. This systematic review recommends a Hemoglobin target of >10–11 g/dL and the use of Erythropoietin is adjusted to the patient's condition so that the choice is more cost effective.